Mitochondria-targeted antioxidant SkQT1 decreases trauma-induced neurological deficit in rat and prevents amyloid-β-induced impairment of long-term potentiation in rat hippocampal slices. (May 2015) - Genrikhs, Elisaveta E.; Stelmashook, Elena V.; Popova, Olga V.; Kapay, Nadezhda A.; Korshunova, Galina A.; Sumbatyan, Natalya V.; Skrebitsky, Vladimir G.; Skulachev, Vladimir P.; Isaev, Nickolay K.
Abstract This study assesses a protective effect of a mitochondria-targeted antioxidant SkQT1 (a mixture of 10-(6'-toluquinonyl) decyltriphenylphosphonium and 10-(5'-toluquinonyl) decyltriphenylphosphonium in proportion of 1.4:1), using an open focal trauma model of the rat brain sensorimotor cortex and a model of amyloid-beta1-42 (Abeta)-induced impairment of hippocampal long-term potentiation (LTP), a kind of synaptic plasticity associated with learning and memory. It was found that a trauma-induced neurological deficit could be partially improved with daily intraperitoneal injections of SkQT1 (250 nmol/kg) for 5 days after the trauma. Neither an analog of SkQT1 without thymoquinone (C12TPP) nor original thymoquinone without a cation residue was effective to improve such conditions. In the SkQ molecule, the phosphonium cation can be replaced by the rhodamine 19 cation, with the SkQTR1 being still active in the treatment of the neurological deficit. Application of 200 nM Abeta to rat hippocampal slices impaired the induction of LTP in the hippocampal CA1 pyramidal layer. A single intraperitoneal injection of SkQT1 (250 nmol/kg body weight) made 24 h before the slice preparation prevented the harmful effect of Abeta on the LTP. Thus mitochondria-targeted antioxidants, containing thymoquinone, have neuroprotective properties.